Exploration of online discussion forum on reading EST texts for ESL learners - Ruhil Amal, Azmuddin; Mazura, Jamalai; Azwin Arif, Abdul Rahim; Mohammad Musab, Azmat Ali; Nor Yazi, Khamis (UUM Press, 2022)
Purpose: This study explored ESL learners’ utilization of Online Discussion Forums (ODFs) in Interactive Reading for Academic Disciplines (iREAD) to assist reading of online scientific texts within an English for Specific Purposes course at a public university.